Woman suffrage and citizenship in the Midwest, 1870-1920 - Egge, Sara (Iowa City, IA : University of Iowa Press, 2018)
Historian Sara Egge offers critical insights into the woman suffrage movement by exploring how it emerged in small Midwestern communities--in Clay County, Iowa; Lyon County, Minnesota; and Yankton County, South Dakota. Examining this grassroots activism offers a new approach that uncovers the sophisticated ways Midwestern suffragists understood citizenship as obligation. These suffragists, mostly Yankees who migrated from the Northeast after the Civil War, participated enthusiastically in settling the region and developing communal institutions such as libraries, schools, churches, and parks. Meanwhile, as Egge's detailed local study also shows, the efforts of the National American Women's Suffrage Association did not always succeed in promoting the movement's goals. Instead, it gained support among Midwesterners only when local rural women claimed the right to vote on the basis of their well-established civic roles and public service. By investigating civic responsibility, Egge reorients scholarship on woman suffrage and brings attention to the Midwest, a region overlooked by most historians of the movement. In doing so, she sheds new light onto the ways suffragists rejuvenated the cause in the twentieth century.
Intro; Contents; Acknowledgments; Introduction. Citizenship, Community, and Civic Responsibility in the Midwest; Chapter 1. Hardship and Bounty: Building Midwestern Communities; Chapter 2. Humble Beginnings: How Midwestern Women Claimed Civic Activism; Chapter 3. Gender, Citizenship, and the Struggle to Achieve Woman Suffrage, 1880â#x80;#x93;1900; Chapter 4. Woman Suffrage as an Obligation: Civic Responsibility and Citizenship, 1900â#x80;#x93;1916; Chapter 5. Fighting for Democracy: Woman Suffrage, Loyalty, and World War I; Conclusion. Remembering Woman Suffrage: Gender and Midwestern Identity; Notes.
Online resource; title from PDF title page (EBSCO, viewed February 12, 2018).
Includes bibliographical references and index.
JSTOR
Keywords: Rural women -- Suffrage -- Iowa -- History; Women -- Suffrage -- Iowa -- History; Suffragists -- Iowa -- Biography; Femmes en milieu rural -- Suffrage -- Iowa -- Histoire; Femmes -- Suffrage -- Iowa -- Histoire; Suffragettes -- Iowa -- Biographies; POLITICAL SCIENCE -- Political Process -- Elections; POLITICAL SCIENCE -- Political Process -- General; HISTORY -- United States -- State & Local -- Midwest (IA, IL, IN, KS, MI, MN, MO, ND, NE, OH, SD, WI); Suffragists; Women -- Suffrage; Iowa; Electronic books; Biographies; History